Kebijakan Moneter dan Transformasinya - Zaky Raihan; Muhammad Fajri Asshidiqy; Muhammad Hilman Haetami; Rasidah Novita Sari (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
Monetary policy is a vital instrument in managing a country's economic stability. Global economic transformation and dynamics in financial markets require in-depth evaluation of monetary policy. This research aims to analyze the influencing factors of monetary policy and investigate the impact of its transformation in the current economic context. Through a careful methodological approach, this research uses secondary data analysis from various global and national economic sources. The literature review investigates the current literature on monetary policy and economic transformation. The results of the data analysis provide deep insight into the factors influencing monetary policy and the consequences of its transformation. The main findings show that changes in the global economic order, financial technology and capital market dynamics play a major role in changing the monetary policy paradigm. This transformation can have a significant impact on economic stability and societal welfare. The conclusions of this research provide a basis for developing policies that are responsive and adaptive to economic transformation. The practical implications of this research include the need to update a more dynamic monetary policy strategy to answer new challenges in the era of globalization. It is hoped that further research will deepen specific aspects of monetary policy transformation to provide a more comprehensive view.